2000
DOI: 10.1002/1098-1004(2001)17:1<42::aid-humu5>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of mutations causing retinitis pigmentosa and other inherited retinopathies

Abstract: Inherited retinopathies are a genetically and phenotypically heterogeneous group of diseases affecting approximately one in 2000 individuals worldwide. For the past 10 years, the Laboratory for Molecular Diagnosis of Inherited Eye Diseases (LMDIED) at the University of Texas‐Houston Health Science Center has screened subjects ascertained in the United States and Canada for mutations in genes causing dominant and recessive autosomal retinopathies. A combination of single strand conformational analysis (SSCA) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
147
0
3

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 291 publications
(151 citation statements)
references
References 37 publications
1
147
0
3
Order By: Relevance
“…Moreover, P23H is, by far, the most common opsin mutation (8,68). We investigated the P23H-induced disease with modern techniques to improve understanding of its expression, retinal distribution, and rate of progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, P23H is, by far, the most common opsin mutation (8,68). We investigated the P23H-induced disease with modern techniques to improve understanding of its expression, retinal distribution, and rate of progression.…”
Section: Discussionmentioning
confidence: 99%
“…RP manifested predominantly by death of rod photoreceptor cells is a progressive disease characterized by night blindness that progresses to loss of peripheral vision and eventually all useful vision over decades (5). Of more than 100 mutant opsins associated with autosomal dominant RP (adRP), the most frequent mutation is P23H (6), accounting for ϳ10% of human cases (7,8).In vitro studies have shown that the P23H opsin associated with adRP is misfolded and retained in the ER (9 -12). Consequently, this protein is not transported to the cell membrane (12) but instead was degraded by the ubiquitin-proteosome system (13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 To our knowledge, this is the first report of this three amino-acid deletion that interestingly causes a highly variable phenotype within the same family. In addition, it highlights choroidal neovascularisation as a potential complication.…”
Section: Commentmentioning
confidence: 71%
“…In fact, of the scores of mutations reported at each locus, typically 2 or 3 are much more prevalent than others. Focusing specifically on ADRP, Table 3 lists pathogenic mutations which are found in multiple, unrelated families (Sohocki et al 2001,Bowne et al 1999,2002. (Similar findings apply to other forms of inherited retinal disease.)…”
Section: Prevalence Of Disease-causing Mutations Causing Autosomal Domentioning
confidence: 92%